NCERT Solutions Class 10 Maths Chapter2 : PolynomialsExercise 2.11. The graphs of y = p(x) are given in Fig. 2.10 below, for some polynomials p(x). Find the number of zeroes of p(x), in each case. Solution We can find the number of zeroes p(x) has by counting the points of intersection of the graph on Xaxis. By applying this knowledge, we can conclude that the graphs have following numbers of zeroes:
2. Find the zeroes of the following quadratic polynomials and verify the relationship between the zeroes and the coefficients.
Solution Hence, the given polynomial has two zeroes. Verification II. Hence, the given polynomial has two zeroes. Verification III. Hence, the given polynomial has two zeroes. Verification IV. Hence, the given polynomial has two zeroes. Verification V. Hence, the given polynomial has two zeroes. Verification VI. Hence, the given polynomial has two zeroes. Verification 3. Find a quadratic polynomial each with the given numbers as the sum and product of its zeroes respectively.
Solution Exercise 2.31. Divide the polynomial p(x) by the polynomial g(x) and find the quotient and remainder in each of the following :
Solution 2. Check whether the first polynomial is a factor of the second polynomial by dividing the second polynomial by the first polynomial:
Solution Since, the remainder is zero. Therefore, first polynomial is a factor of the second polynomial. Since, the remainder is zero. Therefore, first polynomial is a factor of the second polynomial. Since, the remainder is not zero. Therefore, first polynomial is not a factor of the second polynomial. Solution Putting the two zeroes in (x  a)(x  b) Now, 1/3 and 3x^{2}  5, both are factors of the given polynomial. If we divide 3x^{2}  5 by the given polynomial, we get: Therefore, 3x^{4} + 6x^{3}  2x^{2}  10x  5 = (3x^{2}  5) (x^{2} + 2x + 1) = (3x^{2}  5) [(x^{2} + x + x + 1)] = (3x^{2}  5) [x(x + 1) + 1(x + 1)] = (3x^{2}  5) (x + 1) (x + 1) When (x + 1) = 0 x = 1 and when (x + 1) = 0 x = 1. Hence, the remaining two zeroes of the given polynomial are 1 and 1. 4. On dividing x^{3}  3x^{2} + x + 2 by a polynomial g(x), the quotient and remainder were x  2 and 2x + 4, respectively. Find g(x). Solution We know that, p(x) = g(x) × Quotient + Remainder Therefore, x^{3}  3x^{2} + x + 2 = g(x) × (x  2) + (2x + 4) x^{3}  3x^{2} + x + 2 + 2x  4= g(x) × (x  2) x^{3}  3x^{2} + 3x  2 = g(x) × (x  2) On dividing x  2 with x^{3}  3x^{2} + 3x  2, we get 5. Give examples of polynomials p(x), g(x), q(x) and r(x), which satisfy the division algorithm and:
Solution I. p(x) = 8x^{2} + 4x + 2 q(x) = 4x^{2} + 2x + 1 g(x) = 2 r(x) = 0 II. p(x) = x^{3}  3x^{2} + 5x  3 q(x) = x  3 g(x) = x^{2}  2 r(x) = 7x  9 III. p(x) = x^{3}  x^{2} + 2x + 3 q(x) = x  1 g(x) = x^{2} + 2 r(x) = 5 Exercise 2.4 (Optional)1. Verify that the numbers given alongside of the cubic polynomials below are their zeroes. Also verify the relationship between the zeroes and the coefficients in each case:
Solution I. Comparing the given polynomial with p(x) = ax3 + bx2 + cx +d, we get a = 2, b = 1, c = 5, d = 2 Now we will check if the given numbers are zeroes of the given polynomial by substituting them for x. Hence, the given numbers are the zeroes of the given polynomial. II. Comparing the given polynomial with p(x) = ax3 + bx2 + cx +d, we get a = 1 , b = 4, c = 5, d = 2 Now we will check if the given numbers are zeroes of the given polynomial by substituting them for x. Hence, the given numbers are the zeroes of the given polynomial. 2. Find a cubic polynomial with the sum, sum of the product of its zeroes taken two at a time, and the product of its zeroes as 2, 7, 14 respectively. Solution 3. If the zeroes of the polynomial x3  3x2 + x + 1 are a  b, a, a + b, find a and b. Solution Comparing the given polynomial with Ax^{3} + Bx^{2} + Cx + D, we get A = 1, B = 3, C = 1, and D = 1 4. If two zeroes of the polynomial x^{4}  6x^{3}  26x^{2} + 138x  35 are 2 √3, find other zeroes. Solution Substituting the two zeroes in (x  a) (x  b) Now, x^{2}  4x + 1 is a factor of the given polynomial. If we divide x^{2}  4x + 1 by the given polynomial, we get: Therefore, x^{4}  6x^{3}  26x^{2} + 138x  35 = (x^{2}  4x + 1) (x^{2}  2x  35) = (x^{2}  4x + 1) (x^{2}  7x + 5x  35) = (x^{2}  4x + 1) {x(x  7) + 5(x  7)} = (x^{2}  4x + 1) (x  7) (x + 5) Hence, the two remaining zeroes will be 7 and 5. 5. If the polynomial x^{4}  6x^{3} + 16x^{2}  25x + 10 is divided by another polynomial x^{2}  2x + k, the remainder comes out to be x + a, find k and a. Solution First, we need to divide x^{4}  6x^{3} + 16x^{2}  25x + 10 by x^{2}  2x + k and find out the remainder. Upon comparing the coefficients, we get two equations First equation  Second equation  Substitute k = 5 Hence, k = 5 and a = 5.
Next TopicClass 10 Maths Chapter 3
